Ingesta de energía y nutrientes en niños de 2-4 años que asisten al programa “Buen Comienzo”, Medellín (Colombia) (2016)
ABSTRACT: At a global and national level, high prevalence of overweight and obesity in children under five years old has been reported. The etiology is multifactorial, but environmental factors such as sedentary lifestyle, as well as eating habits become more important, given the progressive deterioration in the food quality that promotes the overweight in childhood and leads to increased risk of chronic, noncommunicable early. Objective: To describe the intake of food, energy and nutrients in children aged 2-4 years with obesity and healthy children, attending the “Buen Comienzo” Program in the form of institutional care setting. Method: A Cross-sectional study of 111 children with obesity, classified according to IMC > 3 SD, which had were matched by sex, age and type of care, with a child with normal nutritional status, Trained personnel performed the anthropometric assessment and standardized methods, and dietary intake was assessed using 24-hour recall. Student t-test and Mann Whitney test was used in the bivariate analysis and to determinethe pattern of food intake in obese and eutrophic children, Latent Class Analysis (LCA) was performed. Results: All children have a higher intake of calories to their requirements, but there are significant differences as nutritional status, consumption in obese children is 1,632 kcal (IQR: 1,475-1,801kcal) and eutrophics of 1,798 kcal (IQR 1,702-1,632 kcal) (p = 0,00). Children with healthy weight, have a higher intake of macro and micronutrients (p < 0,05); there is a higher intake of protein and micronutrients during the week (p <0,05) and 30% of children did not consume any vegetables and 60% fruit any day prior to the survey and also had a high consumption of sugars. Conclusions: The children subjected to a obesogenic diet, characterized by a low consumption of fruits and vegetables, as well as highly caloric diet with saturated fats and concentrated carbohydrates, that surpasses their daily requirements to gain weight in undesirable.